PENGARUH KAPUR DOLOMIT SEBAGAI ENERGIZER PADA MATERIAL ST 37 PADA PROSES CARBURIZER - Sandi; Sugiyarto Sugiyarto; Sugianto Sugianto (Prosiding Seminar Nasional Inovasi Teknologi Terapan, 2022)
Carburizing is a heat treatment process on the outer layer of the material using carbon as a compaction component. The working principle of this heat treatment is to put carbon around the workpiece when heated with the aim that the carbon will diffuse to the outer layer of the workpiece. In this research, a carburizing process will be carried out with a variety of catalysts on St37 steel. The catalyst variations used were 100% charcoal and 0% lime, 90% charcoal and 10% dolomite lime, 85% charcoal and 15% dolomite lime, 80% charcoal and 20% dolomite lime, 75% charcoal and 25% dolomite lime. To determine the impact of catalyst variations on the carburizing results, a hardness test will be carried out. From the results of research that has been done that a mixture with a variation of 85% charcoal and 25% dolomite lime has the highest average hardness value with a value of 21.5 HRC and the variation of a mixture of charcoal and dolomite lime has a significant effect on the hardness value.